Debugging mixed‐environment programs with Blink. (11th June 2014) - Lee, Byeongcheol; Hirzel, Martin; Grimm, Robert; McKinley, Kathryn S.
Summary Programmers build large‐scale systems with multiple languages to leverage legacy code and languages best suited to their problems. For instance, the same program may use Java for ease of programming and C to interface with the operating system. These programs pose significant debugging challenges, because programmers need to understand and control code across languages, which often execute in different environments. Unfortunately, traditional multilingual debuggers require a single execution environment. This paper presents a novel composition approach to building portable mixed‐environment debuggers, in which an intermediate agent interposes on language transitions, controlling and reusing single‐environment debuggers. We implement debugger composition in Blink, a debugger for Java, C, and the Jeannie programming language. We show that Blink is (i) simple: it requires modest amounts of new code; (ii) portable: it supports multiple Java virtual machines, C compilers, operating systems, and component debuggers; and (iii) powerful: composition eases debugging, while supporting new mixed‐language expression evaluation and Java native interface bug diagnostics. To demonstrate the generality of interposition, we build prototypes and demonstrate debugger language transitions with C for five of six other languages (Caml, Common Lisp, C#, Perl 5, Python, and Ruby) without modifications to their debuggers. Using real‐world case studies, we show that diagnosing language interface errors require prior single‐environment debuggers to restart execution multiple times, whereas Blink directly diagnoses them with one execution. Copyright © 2014 John Wiley & Sons, Ltd.